Students’ Perceptions of Using TikTok Application in Improving Pronunciation - Silaban, Dewi Azeng Kartini Br.; Marpaung, Marlin Steffi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The research aims to explore students’ respond toward the use of TikTok in mastering English pronounciation skills, to find out students’ perception in learning English pronounciation through the use of TikTok, and to know the effectiveness of TikTok in learning pronunciation. The study employed a quantitative approach. The instument used in this study was a questionnaire with 30 statements by using a Likert scal to gather the data from 84 students in various study programs at Universitas Advent Indonesia. The results indicated that students have a positive perception of using TikTok for English pronunciation practice. This is indicated by how the UNAI students responded, 45% of student that TikTok can be used to master English pronunciation. 45% sudent also agree that TikTok can be used to learn English pronunciation. Lastly 45% student also agree that TikTok is effective for learning pronunciation for UNAI students. In conclusion, the findings suggest that TikTok can be an effective tool for improving English pronunciation skills among university students.